Effects of allopurinol and steroids on inflammation and oxidative tissue damage in experimental lens induced uveitis: a biochemical and morphological study. Issue 5 (May 1996) - Augustin, A J; Spitznas, M; Sekundo, W; Koch, F; Lutz, J; Meller, D; Grus, F H; Wegener, A; Blumenröder, S H
Abstract : AIMS: To evaluate the effects of allopurinol in lens induced uveitis (LIU) by morphological methods and to compare these effects with those of steroids and a combination of both drugs biochemically and morphologically. METHODS: Lipid peroxides (LPO) of the retinal tissue were determined by two different methods (thiobarbituric acid assay (TBA) and high performance liquid chromatography expressed as malondialdehyde-like substances). Myeloperoxidase (MPO) activity in the iris/ciliary body complex was analysed spectrophotometrically. Histological changes on three morphological levels of LIU eyes were evaluated. RESULTS: Both allopurinol and the combination of allopurinol/prednisolone led to a significant reduction in the increaed retinal LPO values. Prednisolone only revealed significant effects on retinal LPO when being measured with the TBA method. MPO activity in iris and ciliary body was significantly reduced in all therapy groups. The morphological evaluation of the sections by two masked investigators revealed a significant reduction (p < 0.05) in the inflammation score in all therapy groups. Morphometric studies using the QUANTIMED system (Leica, Cambridge) showed significantly reduced values (p < 0.05) in the allopurinol group and in the group receiving prednisolone and allopurinol. Prednisolone alone did not lead to a significant reduction in the values. CONCLUSIONS: The findings show that both allopurinol and steroids exert positive effects on the variables determined in LIU. The effects of steroids are believed to be mostly due to their direct action on inflammatory cells. The recently reported scavenging effects of methylprednisolone should play a minor role in this disease model. Allopurinol and oxypurinol act as direct scavengers of free radicals and hypochlorous acid, which is produced via MPO catalysis, thus leading to a reduction in tissue inflammation and tissue damage.